2022
DOI: 10.1136/bmjopen-2021-056135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of multimorbidity in chronic diseases in Guangzhou, China: a data mining study in the residents’ health records system among 31 708 community-dwelling elderly people

Abstract: ObjectivesExamination of the prevalence, influence factors and patterns of multimorbidity among the elderly people in Guangzhou, China.DesignCross-sectional study.Participants31 708 community-dwelling elderly people aged 65 and over.Primary and secondary outcome measuresPrevalence, influence factors and patterns of multimorbidity in seven chronic conditions among the participants. A multistage, stratified random sampling was adopted for selection of health records in the residents’ health records system of Gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We found that the prevalence of multimorbidity was 40.69% in our sample from three survey areas in Guangdong province, which is consistent with the range of the overall prevalence in Guangdong province (9,28,29). One finding in this study that is worthy of particular attention is the regional difference: the prevalences among coastland and mountain residents were higher than those among island residents.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the prevalence of multimorbidity was 40.69% in our sample from three survey areas in Guangdong province, which is consistent with the range of the overall prevalence in Guangdong province (9,28,29). One finding in this study that is worthy of particular attention is the regional difference: the prevalences among coastland and mountain residents were higher than those among island residents.…”
Section: Discussionsupporting
confidence: 88%
“…It uses the prior knowledge of the nature of frequent itemsets, and exhausts all frequent itemsets in the data set through the iterative method of layer-by-layer search, thus mining the potential links of the data. Applying association rules to chronic comorbidity can explore the pattern of chronic comorbidity and obtain the causal relationship among chronic diseases (30,31). Support, confidence, and lift are commonly used metrics for association rules.…”
Section: Principle Of Association Rulesmentioning
confidence: 99%
“…Hypertension ranks among the most prevalent chronic conditions among the older adult population in China. A study investigating seven chronic diseases among older adults in Chinese communities revealed hypertension as the most prevalent condition, with 50% of the surveyed participants reporting hypertensive disorders ( 4 ). Older adults with hypertension inherently have a more delicate constitution compared to their healthier counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in network analysis outcomes across prior studies highlighted the substantial dissimilarities in results among diverse populations, making it inappropriate to generalize findings across populations ( 23 ). In China, there is a substantial and rapidly expanding population of older adults affected by hypertension, who are considered highly susceptible to depression and anxiety disorders ( 3 , 4 ). Nevertheless, the relationship between particular symptoms of depression and anxiety in the hypertensive older adult population remains unclear and has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%